Principlist and Personalist Bioethics: A descriptive analysis and its implications for the discussion on euthanasia (Research, Society and Development, 2025)
The objective of this study is to analyze euthanasia from a bioethical perspective, according to the principlist (Beauchamp Childress) and personalist (Sgreccia) schools of thought. Bioethics examines ethical issues in health and life sciences, addressing dilemmas such as euthanasia. Data were collected from secondary sources, including scientific articles and specialized books. A systematic search was conducted in the SciELO, MEDLINE, BVS, and Lilacs databases, using keywords such as “bioethics,” “principlist bioethics,” “personalist bioethics,” “euthanasia,” and “distanasia.” Initially, this article provides a historical overview of the consolidation of bioethics as a science, highlighting the influence of principlism and its four principles: autonomy, non-maleficence, beneficence, and justice, as well as critiques of this model. Next, the concept of the human person is analyzed to support the implications of the term on personalism and its currents, highlighting the ontologically based bioethics of Elio Sgreccia and its principles: defense of physical life; totality or therapeutic; freedom and responsibility; sociality and subsidiarity. The debate on euthanasia involves a reflection on death, as it can be related to the suffering of serious, chronic, or degenerative diseases, which raises important ethical challenges related to the preservation of human dignity. Finally, the concept of euthanasia is discussed in relation to the bioethical principles of each model and how these can inform and guide the development of a more secure and enriching position on euthanasia.